Medical School Experiences Shape Women Students’ Interest in Orthopaedic Surgery - O’Connor, Mary I. (Clin Orthop Relat Res, 2016)
BACKGROUND: Orthopaedic surgery now has the lowest percentage of women in residency programs of any surgical specialty. Understanding factors, particularly those related to the medical school experience, that contribute to the specialty’s inability to draw from the best women students is crucial to improving diversity in the profession. QUESTIONS/PURPOSES: (1) Does required medical school exposure to orthopaedic surgery increase the proportion of women choosing the specialty? (2) Do negative perceptions deter women from choosing orthopaedic surgery? (3) What proportion of orthopaedic faculty members are women, and what proportion of residents are women? (4) To what degree has gender bias been identified in the application/interview process? METHODS: Two PubMed searches of articles between 2005 and 2015 were performed using a combination of medical subject headings. The first search combined “Orthopaedics” with “Physicians, women” and phrases “women surgeons” or “female surgeons” and the second combined “Orthopedics” with “Internship & Residency” or “exp Education, Medical” and “Sex Ratio” or “Sex Factors”, resulting in 46 publications of which all abstracts were reviewed resulting in 11 manuscripts that were related to the research questions. The Google Scholar search of “women in orthopaedic surgery” identified one additional publication. These 12 manuscripts were read and bibliographies of each reviewed with two additional publications identified and included. RESULTS: Required exposure to orthopaedics was found to be positively associated with the number of women applicants to the field, whereas negative perceptions have been reported to deter women from choosing orthopaedic surgery. Orthopaedics has the lowest percentage of women faculty and women residents (14%) compared with other specialties; this suggests that same gender mentorship opportunities are limited. For women applying to orthopaedics, gender bias is most evident through illegal interview questions, in which women are asked such questions more often than men (such as family planning questions, asked to 61% of women versus 8% of men). CONCLUSIONS: Successful recruitment of women to orthopaedic surgery may be improved by early exposure and access to role models, both of which will help women students’ perceptions of their role in field of orthopaedic surgery.